(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
Benang Merah Bertaut Paku is a dance choreography that addresses psychological violence within the family as one of the main causes of anxiety disorder in children. Psychological violence often leaves no visible physical wounds, yet it has long-term effects on children’s mental health, such as fear, anxiety, pressure, and social isolation. Through the medium of dance, this work seeks to give voice to emotional wounds that are often hidden and rarely discussed openly. The creative process of this work employs dance creation methods consisting of exploration, improvisation, composition, evaluation, and revision. Exploration was conducted to discover movement qualities that represent inner pressure, such as restrained, repetitive, and withdrawn movements. Guided improvisation was used to explore the emotions of children who are ignored and yelled at by their parents. Supporting elements such as tin plates as a symbol of verbal outbursts, white cloth as a symbol of emotional bondage, minimalist music, and dim lighting were used to strengthen the psychological atmosphere of the work. The result of this choreography shows that dance can function not only as entertainment and aesthetic expression, but also as a critical and empathetic language toward social realities. The dancer’s body becomes a medium to convey silence, inner tension, and a child’s fundamental need for love and acceptance from the family. It is hoped that this work will raise public awareness of the importance of children’s mental health and the harmful impact of psychological violence within the family environment